The Effectiveness of Reality Therapy in Reducing the Fear of Failure Among X University Students - Nugroho, Syaqina; Saniatuzzulfa, Rahmah (Universitas Islam Indonesia, 2025)
In the emerging adulthood phase, parental psychological control can cause an increase in the fear of failure among students, as they are afraid of disappointing their parents or being perceived as less competent. Therefore, this research aimed to determine the effectiveness of reality therapy in reducing the fear of failure among students at X University in Indonesia. Using the WDEP (Wants, Doing & Direction, Evaluation, Planning) framework, reality therapy could make students develop strategies to pursue personal goals they are afraid of failing to achieve. A total of 24 students from X University were selected as participants through purposive sampling. An experimental design was used, incorporating a pretest-posttest control group framework. Data were collected using the Performance Failure Appraisal Inventory (PFAI). The collected data were analyzed using the nonparametric Wilcoxon Signed-Rank and Mann-Whitney U tests. The results showed that reality therapy effectively reduced the fear of failure among students, with the effect sustained for 15 days (p < .05). In addition, a significant difference was observed in the reduction of the fear of failure between the experimental and control groups (p < .05). In summary, this research suggested that reality therapy could be an effective intervention to reduce the fear of failure.